2024 update: european consensus statement on gene therapy for spinal muscular atrophy - Kirschner, Janbernd; Bernert, Günther; Butoianu, Nina; De Waele, Liesbeth; Fattal-Valevski, Aviva; Haberlova, Jana; Moreno, Teresa; Klein, Andrea; Kostera-Pruszczyk, Anna; Mercuri, Eugenio; Quijano-Roy, Susana; Sejersen, Thomas; et al. (European journal of paediatric neurology, 2024)
Spinal muscular atrophy (SMA) is one of the most common genetic diseases and was, until recently, a leading genetic cause of infant mortality. Three disease-modifying treatments have dramatically changed the disease trajectories and outcome for severely affected infants (SMA type 1), especially when initiated in the presymptomatic phase. One of these treatments is the adeno-associated viral vector 9 (AAV9) based gene therapy onasemnogene abeparvovec (Zolgensma®), which is delivered systemically and has been approved by the European Medicine Agency for SMA patients with up to three copies of the SMN2 gene or with the clinical presentation of SMA type 1. While this broad indication provides flexibility in patient selection, it also raises concerns about the risk-benefit ratio for patients with limited or no evidence supporting treatment. In 2020, we convened a European neuromuscular expert working group to support the rational use of onasemnogene abeparvovec, employing a modified Delphi methodology. After three years, we have assembled a similar yet larger group of European experts who assessed the emerging evidence of onasemnogene abeparvovec's role in treating older and heavier SMA patients, integrating insights from recent clinical trials and real-world evidence. This effort resulted in 12 consensus statements, with strong consensus achieved on 9 and consensus on the remaining 3, reflecting the evolving role of onasemnogene abeparvovec in treating SMA.
Online verfügbar: 8. Juni 2024, Artikelversion: 14. Juni 2024
Gesehen am 27.02.2025